2010
DOI: 10.1107/s1600536810014789
|View full text |Cite
|
Sign up to set email alerts
|

(4-Carbamoylphenyl)boronic acid

Abstract: In the title compound, C7H8BNO3, the mol­ecule lies on an inversion center leading to a statistical disorder of the B(OH)2 and CONH2 groups. In the crystal structure, mol­ecules are linked by N—H⋯O and O—H⋯O hydrogen bonds, forming sheets parallel to the bc plane. The B(OH)2 and CONH2 groups are twisted out of the mean plane of the benzene ring by 23.9 (5) and 24.6 (6)°, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…6i In the crystal structure of IJ4-carbamoylphenyl)boronic acid, the boronic acid and carboxamide functions are linked through amide-amide and BIJOH) 2 ⋯IJHO) 2 B homosynthons, respectively. 11 On the basis of this knowledge and considering potential applications, we decided to explore herein the formation of cocrystals of aromatic boronic acids with biologically and/or pharmaceutically relevant molecules containing COO − or CIJO)NH 2 functions. For this purpose, the L-series of essential amino acids (AA) and the positional isomers of nicotinamide (NA and INA) were chosen.…”
Section: Introductionmentioning
confidence: 99%
“…6i In the crystal structure of IJ4-carbamoylphenyl)boronic acid, the boronic acid and carboxamide functions are linked through amide-amide and BIJOH) 2 ⋯IJHO) 2 B homosynthons, respectively. 11 On the basis of this knowledge and considering potential applications, we decided to explore herein the formation of cocrystals of aromatic boronic acids with biologically and/or pharmaceutically relevant molecules containing COO − or CIJO)NH 2 functions. For this purpose, the L-series of essential amino acids (AA) and the positional isomers of nicotinamide (NA and INA) were chosen.…”
Section: Introductionmentioning
confidence: 99%
“…The BBA crystal was obtained by dissolving BBA in ethanol–water (1:1 in v/v) solution and slow evaporation in refrigerator (4–8 °C) for 2–3 weeks. The CPBA crystal was grown according to the literature procedure …”
Section: Methodsmentioning
confidence: 99%
“…The CPBA crystal was grown according to the literature procedure. 49 2.3. Spectroscopic Measurements.…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned before, CAPBA had been investigated for its crystallographical structure via single-crystal X-ray spectroscopy (Apostolova et al, 2010). Both the experimental and the calculated bond lengths and bond angles have been tabulated in Table 1 and Table 2 respectively.…”
Section: Molecular Structurementioning
confidence: 99%
“…CAPBA is a white to Brown solid with a melting point of 229-234°C (URL1). Apostolova et al experimentally found the molecular properties of the title compound 4-Carbamoylphenylboronic acid (AKA 4-Aminocarbonylphenylboronic acid / CAPBA) in a crystallographic study (Apostolova et al, 2010). But unfortunately, there is no other experimental spectral data for this compound so far.…”
Section: Introductionmentioning
confidence: 99%